2017
DOI: 10.1007/s40430-017-0803-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the steady-state performance of hydrostatic drives used in the rotary head of the drill machine

Abstract: Hydrostatic drive • Bondgraph modeling • High speed low torque (HSLT) • Low speed high torque (LSHT) • Hydro-motor • Loss coefficients • Slip • Torque loss • Efficiency • Rock strength List of symbols D p Volume displacement rate of the pump (m 3 /rad) D pmax Maximum volume displacement rate of the pump (m 3 /rad) D mh,ml Volume displacement rate of the HSLT or LSHT hydro-motor (m 3 /rad) J ld Generalized load inertia of the driving shaft (Kg m 2) J ldh,ldl Load inertia of the HSLT or LSHT driving shaft (kg m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…For the more detailed diagram and the working principle of the test set-up, the reader can refer to the article proposed by Vardhan et al. 11
Figure 2.(a) Physical system for the low-torque high-speed (LTHS) drive. (b) Physical system for the high-torque low-speed (HTLS) drive.
…”
Section: The Physical Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…For the more detailed diagram and the working principle of the test set-up, the reader can refer to the article proposed by Vardhan et al. 11
Figure 2.(a) Physical system for the low-torque high-speed (LTHS) drive. (b) Physical system for the high-torque low-speed (HTLS) drive.
…”
Section: The Physical Systemmentioning
confidence: 99%
“…The pressure, torque, flow and speed values are obtained through separate sensors and stored and recorded in the PC through the data acquisition (DAQ) system. For the more detailed diagram and the working principle of the test set-up, the reader can refer to the article proposed by Vardhan et al 11…”
Section: The Physical Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they have also checked the experimental validation of the empirical relation in case of actual drilling pertaining to the blasthole drills. Vardhan et al 8 have provided an extensive analysis based on the comparison of the steady-state performance of hydraulic drives linked with a drill machine employed in mining operations. They have devised twin closed-circuit hydraulic drives intended for the drill machine’s rotary head.…”
Section: Introductionmentioning
confidence: 99%
“…Vardhan and Dasgupta 9 have also developed the efficiency map pertaining to the hydraulic drive intended for the drill machine’s rotary head and concluded that the higher efficiency corresponding to the drive is attained near medium to high torque and high speed range. In the above-mentioned studies, 79 the dynamic performance of the hydraulic drives for the rotary head of the blasthole drilling machine has not been addressed. In this respect, further study in the drill dynamics of the system is needed.…”
Section: Introductionmentioning
confidence: 99%